Why do takeover targets protect acquirers? Evidence from force‐the‐vote provisions. Issue 3 (26th February 2021) - Gogineni, Sridhar; Puthenpurackal, John
Abstract: We conduct the first comprehensive study of force‐the‐vote (FTV) provisions in mergers and acquisitions transactions and test competing agency and efficient contracting explanations for their usage. Target FTV provisions are observed more frequently when bidding is costly and are associated with higher target returns, a lower likelihood of competing bids, and a higher likelihood of deal completion. By providing greater deal protection to acquirers, target FTV provisions appear to improve bidding incentives resulting in higher target returns consistent with efficient contracting. Our results are robust to controlling for other merger provisions, such as termination fee provisions, stock voting agreements, and endogeneity concerns.